2014
DOI: 10.1186/1471-5945-14-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b induces cellular senescence in malignant melanoma

Abstract: BackgroundMicro RNAs (miRs) have emerged as key regulators during oncogenesis. They have been found to regulate cell proliferation, differentiation, and apoptosis. Mir-125b has been identified as an oncomir in various forms of tumours, but we have previously proposed that miR-125b is a suppressor of lymph node metastasis in cutaneous malignant melanoma. Our goal was therefore to further examine this theory.MethodsWe used in-situ-hybridization to visualise miR-125b expression in primary tumours and in lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…We first predicted that LINC00152 was a potential target of miR‐125b, as the same binding site was also found in MCL‐1 and miR‐125b, which had a verified targeting relationship . LINC00152 was located in the cytoplasm, just as observed with miR‐125b and MCL‐1, which provides the necessary conditions for endogenous competition . Second, we proved that miR‐125b was negatively correlated with LINC00152 in ovarian cancer tissues, while MCL‐1 was positively correlated.…”
Section: Discussionmentioning
confidence: 61%
“…We first predicted that LINC00152 was a potential target of miR‐125b, as the same binding site was also found in MCL‐1 and miR‐125b, which had a verified targeting relationship . LINC00152 was located in the cytoplasm, just as observed with miR‐125b and MCL‐1, which provides the necessary conditions for endogenous competition . Second, we proved that miR‐125b was negatively correlated with LINC00152 in ovarian cancer tissues, while MCL‐1 was positively correlated.…”
Section: Discussionmentioning
confidence: 61%
“…We did not observe this phenomenon in normal HMEC cells. While it has been previously reported that miR-125b targets and reduces JUN expression during granulocyte differentiation 33,42 and promotes cellular senescence in melanoma 57 , this is the first report identifying these two genes interacting within the same regulatory network to confer γ-irradiation sensitivity in breast cancer. We also identified miR-125b regulated genes involved in stress-response MAPK signaling, which are induced in cancer cells after γ-irradiation, presumably to promote cell survival.…”
Section: Discussionmentioning
confidence: 76%
“…The role of miR-125b in modulating irradiation-sensitivity in breast cancer is most likely a cell-context specific phenotype, given miR-125b itself has been described as a tumor suppressor in breast cancer 37,5456 , melanoma 57 , and bladder cancer 58 , but also as an oncogene in prostate cancer 59 and leukemia 60,61 . miR-125b has also been shown to promote stem cell-like properties in cholangiocarcinoma 62 and expand progenitor cell populations in acute megakaryoblastic leukemia 63 .…”
Section: Discussionmentioning
confidence: 99%
“…4, miRNAs can control cell cycle progression after DNA damage by targeting CHK1 [70][71][72][73][74], p53 [75,76], retinoblastoma 1 serine phosphates from human chromosome 3 (RBSP3) [77], cyclin D [73,78,79], CDC25a [80][81][82], p21, CDK2 [83][84][85], WEE1, PLK1, and so on. One study showed that RBSP3 is a target gene of miR-100.…”
Section: Mirnas Regulate Ddr Effectorsmentioning
confidence: 99%